IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN THE PRACTICE OF ATHLETE TRAINING (Uzbekistan Open Conference, 2026)
This article examines modern approaches to the implementation of artificial intelligence in the practice of athlete training. It highlights the potential of intelligent technologies in analyzing the training process, personalizing workloads, monitoring athletes’ functional condition, predicting sports performance, and preventing injuries. Particular attention is paid to the role of digital solutions in improving training efficiency and enhancing decision-making quality in sports management. The study concludes that artificial intelligence is becoming an important tool for improving the system of sports training in the context of the digital transformation of society.